The effect of drying temperature on cup quality of coffee subjected to mechanical drying - Sandeep, T.N.; Channabasamma, B.B.; Gopinandhan, T.N.; Nagaraja, J.S. (Journal of Plantation Crops, 2021)
The objective of the work was to study the effect of drying temperature on cup quality of the robusta coffee subjected to mechanical drying in comparison with conventional sun drying. The robusta coffee processed by wet (parchment coffee) and dry (cherry coffee) methods were subjected to drying at different temperature regimes (40 oC, 50 oC and 60 oC) in a rotary mechanical dryer. The results of the study indicated that as the drying temperature increased, the time of drying reduced. Sun drying of parchment coffee took 48 hours (approximately seven days) to attain the desired moisture content of 11-12 per cent, while mechanical drying reduced the drying time to 16 to 24 hours. Similarly, cherry coffee subjected to sun drying took 88 hours (approximately 15 days), while mechanical drying reduced the drying time to 32 to 48 hours. The cup quality rating of coffee dried by different drying methods revealed that sun-dried robusta parchment coffee scored the highest cup rating. As the drying temperature increased, the cup quality ratings decreased. A similar cup quality rating was also observed with cherry coffee. These results indicate a considerable reduction of drying time when coffee beans are dried in a mechanical dryer. However, there is a need to regulate the drying temperature, which otherwise would negatively impact the quality of coffee. The drying temperature should not exceed 40oC for preserving the innate quality of robusta coffee because the high drying rates provoked by high temperatures can cause damage to the coffee quality due to the damage caused to the cell membranes. Overall, mechanical drying is more advantageous to sun drying in-terms of drying hours (indirectly reduces dependency on manpower) and preservation of innate quality of the coffee.